Feasibility Study of Transforming RSIA Buah Hati into RSU Buah Hati Ciputat: Strategic Expansion for Healthcare Improvement in Tangerang Selatan - Yochanan, Elisha; Wibowo, Markus; W, F Sukma (International Journal of Health Sciences, 2024)
This study investigates the feasibility of transforming RSIA Buah Hati Ciputat into RSU Buah Hati Ciputat, a Type C general hospital. The expansion is driven by the growing healthcare demands in Tangerang Selatan, where population growth and urban development have led to an increasing need for comprehensive medical services. The study evaluates both external factors, such as demographic trends, economic conditions, and regulatory requirements, and internal factors, including the hospital’s current facilities, human resources, and financial status. A mixed-methods approach is employed, combining quantitative data analysis and qualitative insights. Financial analysis is conducted to determine the investment requirements, projected revenue streams, and cost structures, while SWOT analysis is utilized to assess the hospital's strengths, weaknesses, opportunities, and threats. The findings indicate that the expansion is financially viable and strategically advantageous, with strong potential to improve healthcare access and quality in the region. Key recommendations include investing in infrastructure upgrades, enhancing human resources, and securing adequate funding to support the expansion. The study concludes that transforming RSIA Buah Hati into a general hospital is a feasible project that aligns with the healthcare needs of the local community and provides significant opportunities for growth and development.